Detection and tracking of mesoscale eddies in the Mediterranean Sea: A comparison between the Sea Level Anomaly and the Absolute Dynamic Topography fields. Issue 2 (15th July 2021) - Pegliasco, Cori; Chaigneau, Alexis; Morrow, Rosemary; Dumas, Franck
Abstract: Mediterranean Sea eddies are often generated in fixed geographical locations linked to either bathymetric fluctuations, coastline changes, instabilities around islands, or orographic wind forcing. Because of that, the mean circulation exhibits features with the same special scales as the mesoscale field. We provide here a first comparison of eddies detected and tracked using two altimetry products, the Sea Level Anomaly (SLA) and the Absolute Dynamic Topography (ADT), from 2000 to 2015. We showed that more individual eddies and trajectories are detected in the SLA data than in the ADT, having larger radius but lower Eddy Kinetic Energy. The spatial distribution of the mesoscale activity is different between the two data sets: the ADT-detected eddies closely follow the Mean Dynamic Topography (MDT) patterns which include the mean eddy generation sites whereas the SLA-detected eddies show more spatial homogeneity. The larger eddies are generally well detected in both the ADT or the SLA fields, but the numerous smaller and coastal eddies detected in the SLA fields have a tendency to mismatch the ADT detected eddies. Only 20–30% of eddies are detected exclusively in the SLA or the ADT product (i.e. have no collocation in the other field), whereas to 65–80% of the eddies are detected both in the SLA and the ADT fields. The Ierapetra Eddy is a typical example of the limitation of the SLA-detected eddies, as this orographically controlled feature is present in the MDT and thus leads to an artificial cyclonic eddy in the SLA field that shifts around its most frequent position. This study recommends the use of ADT fields for the detection of mesoscale structures in the Mediterranean Sea where the mean circulation and these mesoscale features have the same spatial scale and intensity, and similarly for any other ocean regions where the MDT contains mesoscale patterns. Yet the ADT fields depend on the accuracy of the MDT, and the altimeter-based SLA fields may be preferable in specific locations where the MDT is not reliable.